Analysis of Individual Behavior Through a Psychoanalytical Approach: A Literature Review - Nurul Azmi (Ilmu Inovasi Nusantara, 2023)
This literature review explores the analysis of individual behavior using a psychoanalytical approach, focusing on critical writings that elaborate on the concepts proposed by Sigmund Freud and related thinkers. Through synthesis and analysis of various articles, this research aims to provide an in-depth understanding of how the psychoanalytical approach is employed to delve into the complexity of individual behavior. The findings of this literature review reveal the evolution of psychoanalytical concepts from Freudian theory to contemporary contributions in psychology. There is a detailed exploration of how the id, Ego, and superego play crucial roles in shaping individual behavior. Additionally, the study highlights the use of the psychoanalytical approach in addressing aspects such as internal conflicts, defense mechanisms, and the impact of past experiences. In the context of the literature review, it is evident that the analysis of individual behavior through the psychoanalytical approach provides profound insights into psychological aspects and significantly contributes to understanding the variations in human behavior. This review presents a comprehensive overview of the development of psychoanalytical theory and how this approach continues to be relevant in understanding individual behavior. The practical implications of this review are also discussed, emphasizing its relevance in clinical settings, education, and personal development